Improving Student Reading Comprehension through GIST (Generating Interaction Schemata and Text) Strategy at Islamic Junior High School - Afrilia, Afnadilla; Sukma Dara Damanik, Emeliya (Institut Agama Islam Negeri Palopo, 2024)
This research focuses on improving students' reading comprehension through the GIST strategy at MTS Junior High School in Medan. This research uses quantitative as a research method. Data was collected through a reading comprehension test. The researcher used two tests, By used a pre-experimental design, namely a pre-test, and a post-test. researcher And Sample of the study was 14 students from one class. Tests used in research are multiple-choice questions. The average score of students' reading comprehension performance on the pre-test was -4.286, While on the post-test shows increased to 78.86. By using the GIST strategy, The purpose of this strategy is for students to be able to summarize, make several important points, and use them to compose a summary statement consisting of fifteen words. The result of the research shows that it can improve students' reading comprehension through the GIST (generating interaction schema and text) strategy.